The role of long-chain polyunsaturated fatty acids in the treatment of cancer Cachexia and tumour growth in patients with malignant diseases: A review - Elizabeth A Symington; Gerda J Gericke (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2008)
Recent studies show that ω-3 polyunsaturated fatty acids (PUFAs) have the capacity to modulate cancer outcomes. The body responds to cancer in the same way that it responds to inflammation and wound healing. Nutrients with anti-inflammatory effects could therefore be expected to play a role in cancer treatment. This review focuses on the role of ω-3 PUFAs in tumourigenesis and cancer cachexia. Studies indicate that eicosapentaenoic acid (EPA) supplementation may promote arrest of tumour growth and reduce cell proliferation. Patients need to consume at least 2 g of EPA per day for it to have a therapeutic effect. Positive outcomes related to cachexia include diminished weight loss, increased appetite, improved quality of life and prolonged survival, although there is controversy regarding these clinical outcomes. The effects of ω-3 PUFAs on tumourigenesis and cachexia are viewed in the context of altered lipid and protein metabolism. This altered metabolism usually experienced by cancer patients results in increased formation of proinflammatory eicosanoids and cytokines. Cytokines play an indirect role by stimulating the production of arachidonic acid-derived eicosanoids, which support inflammation, cell proliferation and angiogenesis, and inhibit apoptosis. It can be concluded that ω-3 PUFA supplementation offers a means of augmenting cancer therapy, inhibiting tumourigenesis and possibly contributing to cachexia alleviation.